Assessing Student Learning Needs to Achieve Competency Outcomes in the Master's Program of Early Childhood Islamic Education - Husnul Bahri (AL-ISHLAH: Jurnal Pendidikan, 2024)
The Early Childhood Islamic Education Masters program at Fatmawati Sukarno Bengkulu State Islamic University aims to lead in Early Childhood Education, fostering pious, moderate, and intelligent young learners across Southeast Asia by 2037. Aligning the program's curriculum with these objectives requires a detailed learning needs assessment. This study employed a descriptive qualitative approach using Milles and Huberman's interactive analysis model. Data was gathered through field and library research, focusing on curriculum documents and learning needs from students at UIN Saepuddin Zuhri Purwokerto and UIN Fatmawati Sukarno Bengkulu. Analysis of field data revealed specific learning requirements aligned with the desired graduate profile, emphasizing competencies in religious moderation, pedagogical skills, and early childhood development strategies. These findings provide essential insights for program managers to refine the curriculum, ensuring it meets the professional standards necessary for graduates to excel in Early Childhood Islamic Education. By aligning curriculum development with assessed learning needs, the program can better prepare students to achieve its mission of cultivating well-rounded educators who meet the goals set for 2037.